Imaging Findings of Duodenal Duplication Cyst Complicated with Duodenal Intussusception and Biliary Dilatation - Eduardo Torres Diez; Raúl Pellón Dabén; Juan Crespo Del Pozo; Francisco José González Sánchez (Case Reports in Radiology)
Duodenal duplication cyst is an extremely rare congenital anomaly usually diagnosed in childhood. However, it may remain asymptomatic for a long period. In adults it usually manifests with symptoms related to complications as pancreatitis, jaundice, or intussusception. We present the radiology findings of a patient with a duodenal intussusception secondary to a duplication cyst. The usefulness of the magnetic resonance (MR) in this case is highlighted.